The Effect of Cast Iron Preheating on the Microstructure of Welding Results by Using Cin-2 Electrodes - Sabirin, Ahmad; Purwantono, Purwantono (Teknomekanik, 2020)
Cast iron is commonly found in engineering tools such as machine frames, vise, lathes, planers, pressing tools, V-belt pulleys and others. Cast iron is a metal which is relatively difficult to weld because it contains more than 0.3% carbon. As a matter of fact, a lot of welding workers still experience failure in welding the cast iron, so they require the proper procedures to perform welding on the cast iron like the heat treatment before the welding. This study was aimed at obtaining the effect of preheating variations on the weld joints in which the process of welding the material used the type of open V seam connection. The specimen used was a cast iron with a thickness of 10 mm and the electrode used was the JIS Z 3252 DFCNiFe electrode. The method applied in this research was the microstructure observation testing toward the welding result by using Shielded Metal Arc Welding (SMAW). Based on the results of the study, it can be concluded that by applying the preheating variation treatment on the cast iron welding, there was a change in the microstructure and it was dominated by pearlite-ferrite in the weld metal area. As a result, the rough graphite that looks like roots became smooth after experiencing the preheating treatment because the ferrite was evenly distributed in the heat affected area. To conclude, the most superior specimen for the cast iron preheating among the four specimens was the one with 425oC temperature.